How to differentiate 2x/(x+y) = y, implicitly?

In summary, implicit differentiation involves finding the derivative of an equation where the dependent variable is not explicitly written. The first method involves using the chain rule and the second method involves using the product rule. In both methods, the derivative of a constant is 0. The third question involves using the product rule with 3 terms, where one of the terms is a constant. The fourth question also involves using the product rule with 2 terms, but a sign error was made.
  • #1
gillgill
128
0
differentiate
2x/(x+y)=y

Method1:
2x=xy+y^2
d/dx(2x)=d/dx(xy+y^2)
2=y+xy'+2y(y')
y'=(2-y)/(x+2y)

Method2:
2x/(x + y) = y
y' = [2(x + y) - (2x)(1 + y')]/(x + y)^2
[(x + y)^2 + 2x]y' = 2(x + y) - 2x
y' = 2y/[(x + y)^2 + 2x]

Which method is using "implicit" differentiation?
 
Physics news on Phys.org
  • #2
Both are, but the second is a lot sloppier.
 
  • #3
another question:
x^3+y^3=6xy

3x^2+(3y^3)y'=...?
how do u differentiate 6xy?
 
  • #4
product rule
 
  • #5
gillgill said:
how do u differentiate 6xy?
Product rule! :wink:
 
  • #6
i only learned how to differentiate using prodct rule with two terms...is it the same with 3 terms?
 
  • #7
6 is a constant, don't even worry about it.
 
  • #8
so...(6xy')+(6y)...?
 
  • #9
6xy

u(x) = 6x, v(x) = y

(u(x)v(x))' = u'(x)v(x) + v'(x)u(x)
 
  • #10
did i start this right?
x^2+y^2+2x-4y-20=0
2x+(2y)(y')+2+4y'=0
 
  • #11
did i start this right?
x^2+y^2+2x-4y-20=0
2x+(2y)(y')+2+4y'=0

you seem to have made a sign error, but other than that it's okay.
 
  • #12
o..i see it...thanks
 

Similar threads

Replies
9
Views
2K
Replies
3
Views
962
Replies
7
Views
1K
Replies
3
Views
1K
Replies
13
Views
665
Back
Top